Mapping global value chains - Koen De Backer; Sébastien Miroudot (European Central Bank (ECB), 2014)
World trade and production are increasingly structured around “global value chains” (GVCs). The last years have witnessed a growing number of case studies describing at the product level how production is internationally fragmented, but there is little evidence at the aggregate level on the prevalence of GVCs. The main objective of this paper is to provide for more and better evidence allowing to examine the position of countries within international production networks. We propose a number of indicators that give a more accurate picture of the integration and position of countries in GVCs, as well as a more detailed assessment of the value chain in four broad industries: agriculture and food products, motor vehicles, electronics and business services.
Keywords: F14; F23; L16; L23; 330; global value chains; world trade